Experimental analysis of self-frequency tracking control strategy for inductive power transfer system. (2017) - Jamal, Norezmi; Saat, Shakir
Inductive power transfer (IPT) systems are capable to transfer an electrical power from a power source (transmitter) into electronic devices (receiver) via an air gap. Since the power transmission is based on the induced voltage concept of two inductive resonance coupling coils, the frequency of the driver circuit may dynamically drift away from the designed circuit. Hence, in order to rectify the aforementioned problem, phased lock loop (PLL) circuit is proposed to ensure the frequency of the IPT system that is maintained to operate at its operating frequency which is 1 MHz in this work. The analysis of the IPT system with self-frequency tracking control strategy performance is validated through the experimental works. The experimental results revealed that the efficiency of self-frequency tracking is equal to 92% and the efficiency without tracking is 87% at 10 mm of air gap distance for 0.8 coupling coefficient.